Devlet-içi Çatışmalarda Üçüncü Taraf Aktörler: Suriye İç Savaşında Türkiye’nin Rolü - Fatma Anıl ÖZTOP (Gazi Akademik Bakış)
This research paper focuses on Turkey’s intervention, as a third-party actor at the regional level, to the Syrian conflict. The aim of this study is to reveal how decisive the perception of national security is to Turkey's existing or prospective intervention, and to what extent this situation contributes to the behavior and methods of other actors, who are involved in the conflict. According to this, this study explains the motivations of Turkey to intervene, the methods Turkey used, and Turkey's interactions with other third-party actors in the process. The result of the study indicates that national security phenomenon is the key factor in Turkey's intervention, Turkey's strategies and intervention methods, has changed in line with the behavior of other third-party actors and the dynamics of the conflict.